Beyond the sentence: Shared reading within a high secure hospital - Watkins, Megan; Naylor, Kathryn; Corcoran, Rhiannon (Frontiers in Psychology, 2022)
Ashworth Hospital provides care for inpatients detained under the Mental Health Acts who present a danger to themselves or others. Rehabilitative interventions can help support the best outcomes for patients, their families, care providers, and society. The efficacy of weekly Shared Reading sessions for four patients with experience of psychosis and a history of self-harm was investigated using a 12-month longitudinal case series design. Session data were subjected to psychological discourse analysis to identify discursive strategies employed to accomplish social action and change over the duration of the intervention. Archetypes of interactional achievement across sessions emerged. Broadening of capacity to consider was demonstrated through increased hedging and less declarative language. Increased assertiveness was achieved through reduced generalisation marked by a transition from second-person plural pronouns to more first-person singular pronouns. Avoidance of expression and disagreement strategies diminished over time. In addition, heightened engagement was accomplished through the increased tendency to employ functionally related and preferred responses within adjacency pairs, which mirrored non-verbal communicative strategies. Shared Reading shows promise for promoting the interactional accomplishment for individuals within high secure settings, who are ready to undertake a recovery-related activity. Pathways of interaction should continue to be explored, with consideration to the current study’s strengths and limitations. This study contributes to the understanding of efficacious reading study design and the interactional outcomes of therapeutic reading.